PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN PERCAYA DIRI DAN PRESTASI BELAJAR SISWA - Selvi Susanti (UNIB Press, 2024)
The purpose of this study was to determine: the application of the Two Stay Two Stray cooperative learning model in enhancing Self Confident attitudes in Biologi Subjects in Class XI MIPA 2 the application of the Two Stay Two Stray cooperative learning model can increase Student learning achievement in BiologiSubjects in Class XI MIPA 3 the application of the Two Stay Two Stray cooperative learning model to improve student learning achievement in Biologi Subjects in Class XI MIPA 1. This research uses Classroom Action Research (CAR) and quasi-experimental designs. The subjects were 34 students of class XI MIPA 2 semester 2. For the quasi-experimental sample of class XI MIPA 1 students were 30 people and for the control class were class XI MIPA 3 as many as 30 people. Data collection techniques in this study used observation sheets and tests. The data analysis used values were (1) analysis of the self confident attitude, (2) analysis of the pre-test and post-test, (3) analysis of the t test of student learning achievement. The results showed that (1) the application of the Two Stay Two Stray learning model, can improve students' Self Confident attitudes on Biologi subjects in Lahat 2 High School in 2022 / 2023 Academic Year. (2) the application of the Two Stay Two Stray learning model, can improve student learning achievement and become a separate motivation for students to follow subject matter (3) Two Stay Two Stray learning model, effectively increasing student learning achievement in Biologi subjects.